Incorporating Olympic lifting and resisted jump platform training to improve lower body power - Markwick, W. (Journal of Australian Strength and Conditioning, 2012)
This article will provide practical applications on how to incorporate Olympic Lifting (OL) and Resisted Jumping Platforms such as `Vertimax` to improve lower body power (LBP) and vertical jump (VJ). The findings of this paper show that incorporating OL with `Vertimax` will have positive effects on LBP and VJ when prescribed within a `max strength` or `power` program. This paper will provide recommendations on how to periodise and prescribe this type of power training for beginner, intermediate and elite athletes.